2019
DOI: 10.1039/c9nr01491h
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale J-aggregates of poly(3-hexylthiophene): key to electronic interface interactions with graphene oxide as revealed by KPFM

Abstract: KPFM reveals the critical role of the aggregate structure in P3HT for achieving efficient phototransport properties in P3HT-GO ensembles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The KPFM images ( Figure 3 d–f) show the surface potential (SP) of the corresponding samples, more precisely, the local difference of the Fermi Level with respect to the tip used for imaging, whereby more positive KPFM values (brighter image colors) correspond to more positively charged regions, as explained in detail in the supporting information of a previous publication. 31 To simplify data interpretation and the discussion, in the following, all SP values are given with respect to the silicon substrate, serving as an internal standard in this work. The KPFM images of isolated P3HT NPs ( Figure 3 d) show an excellent correlation of topography and surface potential, exhibiting an SP difference of +350 ± 50 mV for P3HT NPs .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The KPFM images ( Figure 3 d–f) show the surface potential (SP) of the corresponding samples, more precisely, the local difference of the Fermi Level with respect to the tip used for imaging, whereby more positive KPFM values (brighter image colors) correspond to more positively charged regions, as explained in detail in the supporting information of a previous publication. 31 To simplify data interpretation and the discussion, in the following, all SP values are given with respect to the silicon substrate, serving as an internal standard in this work. The KPFM images of isolated P3HT NPs ( Figure 3 d) show an excellent correlation of topography and surface potential, exhibiting an SP difference of +350 ± 50 mV for P3HT NPs .…”
Section: Resultsmentioning
confidence: 99%
“… 28 , 29 More recently, we have shown that the presence of GO sheets, used as an additive in the water phase of a reprecipitation synthesis process, uniquely favors the formation of P3HT chains with an enhanced planar conformation upon the liquid-phase self-assembly process. 30 , 31 This game-changing role of GO thus facilitates the enhanced development of J-aggregates inside the P3HT NPs , being responsible for establishing close interface interactions between P3HT NPs located on GO sheets and the creation of a water-soluble P3HT NPs –GO charge transfer complex with enhanced optoelectronic properties. While in situ reprecipitation processes thus successfully exploit the presence of GO sheets, the influence of GO in emulsion-based self-assembly technologies, which intrinsically require the additional presence of a stabilizing surfactant, on the growing P3HT nanoparticles and their properties needs to be explored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, increasing the doping concentration of C 60 viz., 0.25-0.50 wt% surface roughness along with other microstructural defects are reduced compared to pristine ZnO films, and thus, a downward shift in Fermi energy levels is observed. 3,50 Hence, it is clear from the above discussions that the incorporation of C 60 into ZnO may tailor the various deep or shallow energy levels which may subsequently cause a shift in the Fermi energy level positions. 18 Figure 6 presents the electrical conductivity (σ) measured by the four-probe method of the pristine and C 60 modified ZnO films.…”
Section: = −mentioning
confidence: 99%